Emotional Intelligence in Islamic Education from Al-Ghazali's Perspective for Early Childhood (Current Research in Education: Conference Series Journal, 2024)
The aim of this research is to determine emotional intelligence in Islamic education according to Al-Ghazali's perspective. This research uses the library research method. With a descriptive qualitative approach, this research was published in various books, articles, and other internet literacy media related to emotional intelligence in education, according to Al-Ghazali's perspective as a reference in working on this article. The results of the research are in the form of an explanation of emotional intelligence in education from a general point of view, the perspective of the Al-Qur'an, the content of Yusuf's letter and Al-Ghazali's perspective which is useful for every reader to better recognize the emotional side of himself, as well as to be more familiar with his point of view. Al-Ghazali. The factors that influence emotional intelligence include various elements of life.